2020
DOI: 10.1002/jcp.30039
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of oxidative stress‐induced annulus fibrosus cell and nucleus pulposus cell ferroptosis in intervertebral disc degeneration pathogenesis

Abstract: Ferroptosis is a necrotic form of regulated cell death that was associated with lipid peroxidation and free iron‐mediated Fenton reactions. It has been reported that iron deficiency had been implicated in the pathogenesis of intervertebral disc degeneration (IVDD) by activating apoptosis. However, the role of ferroptosis in the process of IVDD has not been illuminated. Here, we demonstrate the involvement of ferroptosis in IVDD pathogenesis. Our in vitro models show the changes in protein levels of ferroptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
124
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(126 citation statements)
references
References 44 publications
2
124
0
Order By: Relevance
“…Ferroptosis is involved in pathological cell death associated with ischemia-reperfusion injury, stroke, carcinogenesis, kidney injury, and degenerative diseases such as Parkinson's, Huntington's, and Alzheimer's diseases [ 14 ]. Additionally, some studies found that ferroptosis may also play an important role in IVDD [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ferroptosis is involved in pathological cell death associated with ischemia-reperfusion injury, stroke, carcinogenesis, kidney injury, and degenerative diseases such as Parkinson's, Huntington's, and Alzheimer's diseases [ 14 ]. Additionally, some studies found that ferroptosis may also play an important role in IVDD [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the rigor of the definition of ferroptosis is still worth discussing because of its great significance for related pathological diseases. As ferroptosis overlaps with autophagy, apoptosis, and oxidative stress [23][24][25][26], using biochemical ferroptosis biomarkers only to judge the occurrence or participation of ferroptosis is controversial because such a classification cannot exclude the pseudoferroptotic performance caused by other pathological factors.…”
Section: The Characteristics Of Ferroptosismentioning
confidence: 99%
“…Only two studies described senescence ( 24 , 25 ), and one study discussed mitophagy in IDD ( 25 ). Therefore, the important phenotypes mediated by circRNAs, including cellular senescence, autophagy, mitophagy and ferroptosis, in IDD have not been sufficiently illuminated ( 50 , 57 , 66 , 67 ).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%